Impaired sensitivity to thyroid hormones is positively associated to metabolic syndrome severity in euthyroid Chinese adults as revealed by a cross-sectional study - Zhou, Xiong; Zhang, Ye; Li, Zengyao (Frontiers in Endocrinology, 2025)
ObjectiveThyroid hormones (THs) play a pivotal role in regulating metabolism, and their sensitivity may influence the risk of metabolic syndrome (MetS). This study aimed to investigate the association of impaired sensitivity to THs with MetS and MetS severity score (MetSSS) in Chinese euthyroid adults.MethodsA cross-sectional analysis was conducted involving 17,272 health check-up participants. THs sensitivity indices, including Thyroid Feedback Quantile-Based Index (TFQI), Parametric Thyroid Feedback Quantile-Based Index (PTFQI), TSH Index (TSHI), Thyrotropin Thyroxine Resistance Index (TT4RI), and free triiodothyronine/free thyroxine (FT3/FT4) ratio were assessed. Multivariable regression and restricted spline cubic analyses were conducted to explore the association between THs sensitivity indices and MetS and MetSSS. Subgroup analysis was also performed to examine this association stratified by sex and age.ResultsMultivariable logistic regression analysis indicated that MetS risk was positively associated with all impaired THs sensitivity indices (per SD increase) (TFQI: OR=1.20, 95%CI: 1.15-1.25); PTFQI: OR=1.28, 95%CI: 1.23-1.33; TSHI: OR=1.35, 95%CI: 1.29-1.42; TT4RI: OR=1.57, 95%CI: 1.47-1.67; FT3/FT4: OR=1.17, 95%CI: 1.12-1.23)(all P-value<0.001). After adjusting for confounders, compared with the lowest group of MetSSS, individuals in the highest group of MetSSS were positively associated with all impaired THs sensitivity indices (per SD increase) (TFQI: OR=1.16, 95%CI: 1.07-1.21 PTFQI: OR=1.12, 95%CI: 1.06-1.17; TSHI: OR=1.13, 95%CI: 1.06-1.19; TT4RI: OR=1.25, 95%CI: 1.15-1.35; FT3/FT4: OR=1.82, 95%CI: 1.72-1.93). Nonlinear associations were found between THs sensitivity indicators and MetS (P for non-linear<0.001). Subgroup analysis indicated that all thyroid hormones sensitivity indices were positively associated with MetS by gender (male/female) and age (<60 years/≥60 years).ConclusionImpaired sensitivity to THs is associated with an increased risk of MetS and MetSSS in Chinese euthyroid adults. Future research should consider thyroid hormones sensitivity indices in the assessment of MetS risk.